2007
DOI: 10.1093/ndt/gfm534
|View full text |Cite
|
Sign up to set email alerts
|

Cinacalcet (KRN1493) effectively decreases the serum intact PTH level with favourable control of the serum phosphorus and calcium levels in Japanese dialysis patients

Abstract: These results suggest that lower dose levels of cinacalcet, as compared to those in US/EU studies, may be sufficient effectively suppress the serum iPTH levels and allow favourable management of the serum calcium and phosphorus levels in Japanese patients, having a longer average dialysis vintage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
114
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 140 publications
(125 citation statements)
references
References 23 publications
9
114
1
1
Order By: Relevance
“…However, there was no mortality benefit of difference in all cause hospitalization [19]. Another randomised trial to evaluate the effect of cinacalcet hydrochloride to control secondary hyperparathyroidism in Japanese patients, concluded that target iPTH (<250 pg/ml) was achieved in 51.4% in cinacalcet group vs. 2.8% in the control group [23]. The results of our study were similar to above mentioned studies.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…However, there was no mortality benefit of difference in all cause hospitalization [19]. Another randomised trial to evaluate the effect of cinacalcet hydrochloride to control secondary hyperparathyroidism in Japanese patients, concluded that target iPTH (<250 pg/ml) was achieved in 51.4% in cinacalcet group vs. 2.8% in the control group [23]. The results of our study were similar to above mentioned studies.…”
Section: Discussionsupporting
confidence: 87%
“…To evaluate the efficacy of cinacalcet to reduce intact PTH on patients on dialysis, Geoffrey et al [19] observed reduction in calcium and phosphorus by 6.8% and 8.4% respectively. While assessing the effect of cinacalcet to reduce iPTH in Japanese dialysis dependent patients, Fukagawa et al observed significant reduction in serum calcium and phosphorus in the cinacalcet group [23]. In the present study, serum calcium and phosphorus levels significantly increased after cinacalcet introduction.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…During the time that these outcomes improved, the largest change in treatment was the increasing use of cinacalcet (28,29). Within 1.5 years after it first became available (January, 2008) it was being prescribed to 29% of the patients in this study.…”
Section: Mbd Management Status and Treatmentmentioning
confidence: 85%